US Adult Smokers' Perceived Risk of Fire or Explosion-Related Injury Caused by Electronic Nicotine Delivery Systems. (November 2019) - Nyman, Amy L.; Weaver, Scott R.; Huang, Jidong; Slovic, Paul; Ashley, David L.; Eriksen, Michael P.
Objectives: Publicity on incidents of electronic nicotine delivery systems (ENDS) exploding or catching fire may influence smokers' risk perceptions and decisions about using ENDS for quitting smoking. We examined combustible cigarette smokers' perceptions of the possibility of injury from exploding ENDS and the relationship of those perceptions to ENDS use, perceived risk relative to smoking, and perceived costs and benefits of ENDS use. Methods: We used data from the 2017 Tobacco Products and Risk Perceptions Survey of a national probability sample of US adults, conducted online in August and September 2017. The analytic sample consisted of 1181 current combustible cigarette smokers aware of ENDS. Results: Among combustible cigarette smokers aware of ENDS, a medium/high perceived risk of injury from exploding ENDS was associated with lower odds of current ENDS use (adjusted odds ratio [aOR] = 0.50; 95% confidence interval [CI], 0.30-0.86; P = .01), perceiving ENDS to be at least as harmful as cigarettes (aOR = 3.22; 95% CI, 2.11-4.93; P < .001), and feeling that the negatives of ENDS use outweighed the positives (aOR = 3.50; 95% CI, 2.00-6.14; P < .001). Conclusions: Product standards, improved product labeling, and education about how to properly use, charge, and store ENDS can help protect consumers from injury. Communication efforts should seek to fully inform combustible cigarette smokers about both the absolute health risks of ENDS, including risk of explosions, and their relative risks compared with those of cigarette smoking.